Neonatal invasive candidiasis: updates on clinical management and prevention. (January 2022) - Kilpatrick, Ryan; Scarrow, Evelyn; Hornik, Chi; Greenberg, Rachel G
Summary: Neonatal invasive candidiasis is an important cause of morbidity and mortality in preterm infants. The incidence of invasive candidiasis in this population has been declining in high-income settings, largely due to preventive measures, although there are still considerable variations in incidence between health-care centres. Surveillance data and large, multicentre studies in lower-income settings are not available, although preventive measures in these settings have been shown to decrease the incidence of neonatal invasive candidiasis. Understanding risk factors and pathogenesis are key to the prevention of invasive candidiasis. The difficulty of a definitive diagnosis of invasive candidiasis and the high risk for death or substantial neurodevelopmental impairment, even with appropriate treatment, further increase the need for effective preventive measures. In this Review, we examine the pathogenesis, clinical presentation, and diagnosis of invasive candidiasis. We highlight commonly used and emerging preventive and prophylactic measures, including standardised central line care, antibiotic stewardship, antifungal prophylaxis, and probiotics. Finally, we provide updates on empirical treatment, clinical management in confirmed cases of invasive candidiasis, and antifungal pharmacotherapy.